TRANSLATION AND NOTE ON TRANSLATION OF "THE MAN WHO KNEW JAVANESE" BY LIMA BARRETO - Emmanuel Félix François, Michel (Revista de Letras, 2021)
This text is a translation to English of “The man who Knew Javanese” by Lima Barreto with an introductory note. The note on the translation presents a brief overview of the challenges of translating Lima Barreto’s prose, such as the creation of the character as the representational constitution of the society of that time and the author’s style with a creative syntax, which attests to the types portrayed in the narrative. The tone of rascality, which permeates the short story, was one of the objectives sought in the translation. Keywords: Lima Barreto. “The Man Who Knew Javanese”. Translation into English